Subcutaneous Implantable Cardioverter-Defibrillator in A 30Kg Young Child With Hypertrophic Cardiomyopathy - Lopes, Lisete; Sousa, Pedro A.; Andrade, Helena; Rodrigues, Dina; Bernardo, João; Elvas, Luís; Pires., António (Cardiology and Cardiovascular Medicine, 2020)
Hypertrophic cardiomyopathy is the most common heritable cardiomyopathy, being the most frequent cause of sudden cardiac death in the young. Although sudden cardiac death risk stratification criteria have been validated for adults, its application is not recommended in a pediatric population. After considering risks and benefits, choosing the ideal candidate for an implantable cardioverter defibrillator (ICD) for primary prevention purposes still remains a challenge in a child with hypertrophic cardiomyopathy. In children, major issues concerning transvenous ICDs are those related to the lead implantation and the increased risk of systemic infections at mid-long term. With these in mind, it would appear that a subcutaneous ICD, in this population group, is an alternative to be considered. This case regarding a 30Kg, an 8-year-old child with hypertrophic cardiomyopathy highlights the difficulties in sudden cardiac death risk stratification, raises the questions related to which type of ICD to implant and illustrates the feasibility of a subcutaneous ICD in this particular setting.